E-business capabilities and innovation performance: The mediating effect of knowledge management strategies - Arias-Pérez, Jose; López-Zapata, Esteban; Echeverri-Bedoya, Andrea (Serbian Journal of Management, 2020)
The aim of this paper is to analyze the mediating effect of the knowledge management strategies on the relationship between e-business capabilities and innovation performance. The research model was tested with a sample of 102 firms belonging to IT intensive sectors, located in an emerging country that is a regional leader in terms of e-business adoption. Structural equations by the consistent partial least squares method were used. The main result indicates that only the personalization strategy has a partial mediating effect. In conclusion, e-business capability alone is insufficient for achieving a superior innovation performance. This finding also helps consolidate the incipient study perspective that understands knowledge management not as an antecedent variable which becomes indispensable for e-business adoption, but as an organizational factor that intervenes a posteriori and which is focused on achieving an effective use of all the knowledge resulting from the digital operation of the business.